1992
DOI: 10.1007/bf02247426
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute subcutaneous nicotine on attention, information processing and short-term memory in alzheimer's disease

Abstract: This single-blind, placebo controlled study reports on the effects of administering three acute doses of nicotine (0.4, 0.6 and 0.8 mg) subcutaneously to a group of Alzheimer's disease (DAT) patients (n = 22), young adult controls (n = 24), and normal aged controls (n = 24). The study extends our previous findings obtained using smaller groups of subjects. Drug effects were examined on three computerised tests: the first measuring rapid visual information processing, sustained visual attention and reaction tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
225
2
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 442 publications
(234 citation statements)
references
References 33 publications
(24 reference statements)
5
225
2
1
Order By: Relevance
“…Although substantial loss of cholinergic neurons has been demonstrated in AD (Francis et al, 1999), post-mortem studies have shown that some functional nAChRs remain, even at a late stage of the disease (Shimohama et al, 1986;Whitehouse et al, 1986;Schroder et al, 1991;Court et al, 2001;Perry et al, 2001). In agreement with this observation, nicotine, the nonselective prototypical ligand for nAChRs, improves certain cognitive functions in AD patients (Jones et al, 1992;Wilson et al, 1995;White and Levin, 1999;Newhouse et al, 2001;Rezvani and Levin, 2001). Unfortunately, nicotine also exhibits a broad spectrum of undesirable side effects (Benowitz, 1986;Watkins et al, 2000), which limits its use as a therapy.…”
Section: Introductionmentioning
confidence: 95%
“…Although substantial loss of cholinergic neurons has been demonstrated in AD (Francis et al, 1999), post-mortem studies have shown that some functional nAChRs remain, even at a late stage of the disease (Shimohama et al, 1986;Whitehouse et al, 1986;Schroder et al, 1991;Court et al, 2001;Perry et al, 2001). In agreement with this observation, nicotine, the nonselective prototypical ligand for nAChRs, improves certain cognitive functions in AD patients (Jones et al, 1992;Wilson et al, 1995;White and Levin, 1999;Newhouse et al, 2001;Rezvani and Levin, 2001). Unfortunately, nicotine also exhibits a broad spectrum of undesirable side effects (Benowitz, 1986;Watkins et al, 2000), which limits its use as a therapy.…”
Section: Introductionmentioning
confidence: 95%
“…Nicotine administration may just be relieving withdrawal and correcting those deficits. However, if low-dose nicotine is administered to normal nonsmokers, thereby avoiding the confound of withdrawal, there is enhanced performance on the continuous performance test with decreased errors of omission without an increase in errors of commission [62] In Alzheimer's disease, where nicotinic cholinergic receptors are known to be decreased in the cortex and hippocampus [63,64], nicotine injections or nicotine skin patches significantly improve attention, learning and memory [65,66,67,68,69,70]. Similarly, in adults with attention deficit disorder, nicotine skin patch reduces clinical symptoms and increases reaction time, but does not improve errors of omission in the Continuous Performance Test [71].…”
Section: α7 In Learning and Memorymentioning
confidence: 99%
“…The results of most studies reveal that smokers report alleviation of negative affect by smoking, (Brandon and Baker 1991) and increased anxiety during withdrawal. Nicotine also has a stimulant effect on cognitive processes, improving vigilance, enhancing selective attention, and promoting response inhibition to irrelevant stimuli (Jones et al 1992). …”
Section: Introductionmentioning
confidence: 99%